Employees’ Adaptability in Japanese Workplace Cultures (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
All organisations are hoping to have employees that can adapt well to the workplace cultures and remain long in the organisation. One of the organisation's objectives is to have an employee who stays with the company throughout its journey to achieve exceptional performance. However, there are certain barriers that make it difficult for employees to fit in with the workplace culture, which leads to employee turnover, particularly in global corporations. As a result of this scenario, the issue of employees' adaptability in workplace cultures has emerged, with this study focusing on local employees who work in Japanese-based organisations. Therefore, this study has identified four objectives which are designed to examine (1) the level of employee adaptability among local employees that work in Japanese-based organisations; (2) the relationship between communication, innovation, teamwork and decision-making cultures and the employee's adaptability by the local employees; (3) what the best predictor is that contributes towards employee adaptability by the local employees that work in Japanese-based organisations; and (4) the years of experience as a moderator in the relationship between workplace cultures (communication, innovation, teamwork and decision-making) and employee adaptability. This study was conducted among Malaysian employees who work for Japanese-based businesses. Structured questionnaires and stratified random sampling were used. The data was collected from 360 local employees. The study revealed a high level of employee adaptation among local employees working in Japanese-based businesses. The three factors, namely communication, innovation, and teamwork cultures, have a substantial association with employees' adaptability. This study also reveals there is no significant relationship between decision-making culture and employee adaptability.